ASSESSMENT OF THE COMPETITIVE ADVANTAGES OF RETAIL ENTERPRISES AT THE STAGES OF THEIR LIFE CYCLE - CHORNA, Marina; SMOLNYAKOVA, Nataliya; VOLOSOV, Anatoly (Journal of European Economy, 2021)
It is revealed that assessment of competitive advantages of retail enterprises has grown more essential in the conditions of European integration. Approaches to the choice of tools for assessing the competitive advantages of retail enterprises are studied. Their debatable nature, lack of consensus and impossibility of application in retail enterprises without adaptive transformations are revealed. The paper highlights the basic prerequisites for the development of a multi-criteria integrated assessment system: the dual nature of competitive advantages and suitability for a certain stage of their life cycle; specifics of content and typology of competitive advantages of retail trade enterprises as a consequence of the peculiarities of the industry. The authors develop a system for assessing the competitive advantages of retail enterprises with the differentiation of criteria and indicators by stages of the life cycle: establishment, implementation, development. The use of individual and generalized assessment indicators at each stage is substantiated. Economic and mathematical modelling is used to calculate generalizing indicators. It is proposed to use them to assess the competitive indicators of the enterprise: competitive potential, competitiveness and sustainable competitiveness. The system of assessment of competitive advantages at chain retail enterprises has been tested. It is confirmed that the results of research have been adopted by retail enterprises for implementation and have been used to develop measures for the creation, implementation and development of competitive advantages. JEL: C52, C81, L81, O29.